Answer:
G
Step-by-step explanation:
9+(-3) = 6
Answer:
x = 1; y = 6
x = 5; y = 26
x = 8; y = 41
x = 10; y = 51
Step-by-step explanation:
Just substitute the x values
Answer:
Follow along with the pattern, for example if it is going by 2's then you would write a 4
D
Because it is the same while number just with a extra .9
Answer:
y= 3- x/3
Step-by-step explanation:
To find the inverse function, swap x and y, and solve the resulting equation for x.
If the initial function is not one-to-one, then there will be more than one inverse.
So, swap the variables: y=9−3x so it becomes x=9−3y.
Now, solve the equation x=9−3y for y. You would just need to leave y alone so you divide by 3 on both sides (NOT negative 3. Just 3.)